2022
DOI: 10.3389/fpls.2022.849658
|View full text |Cite
|
Sign up to set email alerts
|

Overhauling the Effect of Surface Sterilization on Analysis of Endophytes in Tea Plants

Abstract: Increasing evidence shows that plant Endophytes play a crucial role in the fitness and productivity of hosts. Surface sterilization is an indispensable process before high-throughput sequencing (HTS) and tissue separation of plant endophytes, but its potential impact on the composition and diversity of endophytes has rarely been investigated. In the present work, the influence of sodium hypochlorite (NaClO) on the diversity of endophytic bacteria and fungi in leaves and stems of tea plants was investigated. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Our strain-nested PCR technique also complemented the traditional technique of plating tissue, since the frequent use of sodium hypochlorite to sterilize tissue surfaces may affect the diversity of fungal endophytes [28] or result in non-viable applied endophytes, as observed in our results. Subsequent evaluations will be essential to authenticate the efficacy of this method in the field-based monitoring of single or multiple strains in beans or other plants.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Our strain-nested PCR technique also complemented the traditional technique of plating tissue, since the frequent use of sodium hypochlorite to sterilize tissue surfaces may affect the diversity of fungal endophytes [28] or result in non-viable applied endophytes, as observed in our results. Subsequent evaluations will be essential to authenticate the efficacy of this method in the field-based monitoring of single or multiple strains in beans or other plants.…”
Section: Discussionmentioning
confidence: 69%
“…Techniques to study natural or artificially applied endophytes include direct observation, and culture-dependent and culture-independent methods, in which plant surface microorganisms are first removed [ 27 ]. However, this process may affect the diversity [ 28 ] and viability of endophytes of interest [ 29 ] in the plant. Therefore, it is essential to use culture-independent methods for the accurate and fast detection of endophytes, even if the microorganism is not viable.…”
Section: Introductionmentioning
confidence: 99%
“…Successful methods for endophyte isolation have been reviewed [67,73]. Yu et al [74] studied the effect of different concentrations of sodium hypochlorite employed and exposure times on the efficacy of surface sterilization on endophyte diversity from tea plants (Camellia sinensis). They found that stem and leaf tissues need different conditions, with mature stem tissue requiring a higher concentration and longer exposure time to achieve complete surface sterilization.…”
Section: Isolation Proceduresmentioning
confidence: 99%
“…The excess Collection, Isolation, Culture and Maintenance of A. solani Early blight was characterized by the visualization of leaf lesions and leaf samples with typical symptoms of A. solani were collected from Potato Crop Development Centre (PCDC) Nigale, Sindhupalchowk. Samples were surface sterilized with 1% Sodium hypochlorite for 5 minutes (Yu et al, 2022) and washed three times with distilled water. They were then dried and incubated under a 5 mm thick potato tuber slice on top of a moistened filter paper in petri plates (9 mm Ø) at 24 ± 2 After 24 hrs, fresh sporulation (whitish cottony fungal growth) was visible on abaxial surface of leaves.…”
Section: Collection and Preparation Of Botanical Extractmentioning
confidence: 99%